EXTH-53. TUMOR TREATING FIELDS LEADS TO CHANGES IN MEMBRANE PERMEABILITY AND INCREASED PENETRATION BY ANTI-GLIOMA DRUGS. (11th November 2019) - Chang, Edwin; Patel, Chirag; Beinat, Corinne; Young, Caroline; Flores, Thomas; Zeng, Yitian; Joubert, Lydia; Arami, Hamed; Natarajan, Arutselvan; Sinclair, Robert; Gambhir, Sanjiv
Abstract: BACKGROUND: Efforts are underway to uncover novel, unorthodox therapies against glioblastoma (GBM). Tumor treating fields (TTFields) disrupt mitotic spindle formation and stymie proliferation in tumor cells. Combining TTFields with Withaferin A, synergistically inhibited proliferation in GBM. We wished to uncover the relevant mechanism. METHODS: Human and murine GBM cells (GBM2, GBM39, U87-MG, KR158B) were isolated from primary tumors. Cells were engineered to stably express firefly luciferase (fLuc). Proliferation was assessed by bioluminescence imaging (using D-Luciferin as a substrate for fLuc) or cell counting. Dextran-FITC binding and scanning electron microscopy (SEM) studies were used to probe effects on cellular membranes. RESULTS: TTFields (200 kHz, 4 V/cm) significantly inhibited growth of cells (n=3/time point, p≤0.02; 2-way ANOVA, no TTFields vs. TTFields). Combination of Withaferin A with TTFields significantly inhibited growth of glioma cells synergistically beyond that of Withaferin A or TTFields alone (p< 0.01, at least n=3 experiments). Bioluminescence imaging suggested alterations in membrane configuration when cancer cells were exposed to TTFields. This was validated with observations of greater fluorescence of membrane-associating Dextran-FITC to U87-MG cells that were subjected to TTFields (p< 0.01, 2-way ANOVA, TTFields vs. no TTFields, n=3 experiments). SEM revealed significantly greater and larger number of holes on the membrane surface of TTFields-exposed U87-MG cancer cells (53.5±19.1 holes per field of view and mean size=240.6±91.7 nm2) compared to unexposed cells (23.9±11.0 holes per field of view and mean size=129.8±31.9 nm2, p< 0.005: TTFields exposed vs. non-exposed, n=3 samples, univariate Mann-Whitney test). CONCLUSION: The findings suggest a novel combinatorial approach to treat GBM in a manner that is better than single treatment (drug or TTFields) alone and that is synergistic. Synergy is achieved through TTFields inducing increased permeability on membranes thus conferring greater accessibility to drug. Such a strategy is thus a promising candidate for future clinical translation in glioblastoma.